Chapter Tessere per la memoria sociale del Novecento: gli archivi di Antonio Carbonaro, Andrea Devoto, ANDU (Associazione nazionale docenti universitari) - Boldrini, Enrica (Strumenti per la didattica e la ricerca, 2021)
The contribution illustrates the personal archives of Antonio Carbonaro, sociologist, Andrea Devoto, psychiatrist and the National Association of University Professors (ANDU), testimonies of great importance for the social history of the twentieth century